Battery activator and preparation method thereof, activation film, negative plate, battery, battery pack and electric equipment
By designing a battery activator containing sustained release material, the problem of lithium ion diffusion difficulties caused by damage to the SEI membrane of lithium-ion batteries and excessive additive content is solved, and the battery cycle stability and capacity improvement is achieved.
Patent Information
- Application Number
- CN202411361895.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-09-26
AI Technical Summary
During the recycling of existing lithium-ion batteries, the SEI membrane is easily damaged or decomposed, resulting in a degradation of battery performance. Although high content of additives can continuously repair the SEI film, it will increase the viscosity of the electrolyte, causing difficulties in diffusion of lithium ions and unevenness.
A battery activator is used, which comprises a housing and a sustained-release material encapsulated within the housing, which contains the additives required to form the SEI film. By designing a multi-layered shell, the sustained release rate of the additive is controlled to ensure that the additive concentration is always within the appropriate range.
The uniform distribution of additives in the battery cell is achieved, the cycle life and capacity of the battery are extended, and the difficulty and unevenness of lithium ions caused by excessive additive content are avoided.
Smart Images

Figure CN119786599A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a battery activator and a preparation method thereof, an activation membrane, a negative electrode sheet, a battery, a battery pack and electrical equipment. Background Art
[0002] Solid Electrolyte Interphase (SEI) is a key protective layer in lithium-ion batteries. It is usually formed between the negative electrode material (such as graphite) and the electrolyte. The stability and integrity of the SEI film are crucial to the performance and life of the battery. As the battery is recycled, the SEI film may be damaged or decomposed, resulting in a decrease in battery performance.
[0003] In order to form the SEI film, it is generally necessary to add specific additives to the electrolyte, such as vinylene carbonate (abbreviated as "VC"), etc. In order to continuously repair the damaged or decomposed SEI film, the current conventional method is to increase the content of specific additives. However, too high a content of specific additives will increase the viscosity of the electrolyte, resulting in uneven lithium insertion in the battery cell and increased internal resistance of the battery. Summary of the invention
[0004] The present invention provides a battery activator, which can continuously provide an additive required for forming an SEI film for a battery cell, and can always keep the concentration of the additive within a certain range, thereby avoiding the difficulty and unevenness of lithium ion diffusion caused by excessively high additive content, thereby ensuring the capacity and cycle stability of the battery cell.
[0005] The invention also provides a method for preparing a battery activator, which can prepare the battery activator and is easy to operate.
[0006] The present invention also provides an activation membrane, which can be combined with a negative electrode sheet, a separator, etc., so as to further improve the distribution uniformity of additives required for forming the SEI film in the battery cell, ensuring that the battery cell has a long cycle while having good capacity performance.
[0007] The present invention also provides a negative electrode sheet. Since the surface of the negative electrode sheet includes the above-mentioned activation film, the negative electrode sheet can improve the distribution uniformity of additives required to form the SEI film in the battery cell and maintain the stability of the SEI film, thereby ensuring the long cycle and capacity of the battery cell.
[0008] The present invention also provides a diaphragm, which includes the above-mentioned activation film, so it can improve the distribution uniformity of additives required for forming the SEI film in the battery cell and maintain the stability of the SEI film, thereby ensuring the long cycle and capacity of the battery cell.
[0009] The present invention also provides a battery. Since the battery comprises the negative electrode sheet and / or the activation membrane, the battery has the advantages of long cycle and good capacity.
[0010] The present invention also provides a battery pack. Since the battery pack includes the battery, the battery pack has good electrical performance and a stable cycle life.
[0011] The present invention also provides an electrical device. Since the electrical device includes the above-mentioned solid-state battery or battery pack, the electrical device has good electrical performance and a long service life.
[0012] In detail, in the first aspect, the present invention provides a battery activator, comprising a shell and a sustained-release material encapsulated in the shell; the sustained-release material comprises an additive required for forming a SEI film; the shell comprises a first polymer layer close to the sustained-release material and a second polymer layer away from the sustained-release material, the first polymer layer comprises a plurality of first micropores, the second polymer layer comprises a plurality of second micropores, the second polymer layer comprises a cross-linked polymer formed by cross-linking a CC unsaturated polymer, the pore size of the first micropore is not greater than 0.2 μm, and the pore size of the second micropore is not less than 0.5 μm.
[0013] Furthermore, the sustained-release material is in a semi-gel state or a gel state;
[0014] And / or, and / or, the pore size of the first micropore is 0.001 μm-0.2 μm, and the pore size of the second micropore is 0.5 μm-1 μm.
[0015] Further, the additive required for forming the SEI film includes at least one of vinylene carbonate, propane sultone, methylene disulfate, vinyl ethylene carbonate, and fluoroethylene carbonate;
[0016] And / or, the additive accounts for 50%-70% of the weight of the sustained-release material.
[0017] Furthermore, the first polymer layer includes a polymer substrate and a first additive, the polymer substrate includes at least one of polypropylene, polyvinylbenzene, and polycarbonate; the first additive includes at least one of a sulfonic acid polymer, a phosphate polymer, and a silicon-alkoxy polymer.
[0018] Furthermore, the second polymer layer includes the hydrophobic cross-linked polymer, a second additive and / or a third additive, the second additive includes an isocyanate polymer and / or an epoxy polymer, and the third additive is a silicon-alkoxy polymer.
[0019] Furthermore, the structure of the silicon-alkoxy polymer is as shown in Formula 1:
[0020]
[0021] Wherein, R1 and R2 are each independently one of -OCH3, -N(CH3)CH3, and -NH-R3, R3 is a C1-C20 alkyl group, and n is greater than 0.
[0022] Furthermore, the first additive accounts for 2%-5% of the weight of the polymer substrate.
[0023] Further, the second additive accounts for 2%-5% of the weight of the cross-linked polymer;
[0024] And / or, the third additive accounts for 2%-5% by weight of the cross-linked polymer.
[0025] In a second aspect, the present invention provides a method for preparing the above-mentioned battery activator, comprising the following steps:
[0026] 1) The additives and gelling agent required for forming the SEI film are mixed to obtain a semi-gel or gel-state sustained-release material;
[0027] 2) adding the sustained-release material to a dispersion liquid including a polymer substrate, a first additive, a dispersant, and a solvent, performing a mixing process to obtain a mixed system, and volatilizing the solvent of the mixed system to obtain a sustained-release material wrapped with the first polymer layer; wherein the solid content of the mixed system is 30-40%, and the volatilization rate of the solvent is >2750 cm / h;
[0028] 3) adding the sustained-release material wrapping the first polymer layer to a dispersion liquid including a CC unsaturated polymer, a second additive and / or a third additive, a crosslinking curing agent, and a solvent, and performing a crosslinking reaction at 50° C.-70° C. to obtain the battery activator.
[0029] In a third aspect, the present invention provides an activation membrane formed by the battery activator described in the first aspect.
[0030] In a fourth aspect, the present invention provides a negative electrode sheet, comprising a current collector, and a negative electrode material layer and an activation membrane sequentially disposed on at least one surface of the current collector, wherein the activation membrane is the activation membrane described in the third aspect.
[0031] In a fifth aspect, the present invention provides a diaphragm, which is the activation membrane described in the third aspect; or, comprises a diaphragm base layer and an activation membrane, wherein the activation membrane is arranged on a side of the diaphragm base layer close to the negative electrode sheet, and the activation membrane is the activation membrane described in the third aspect.
[0032] In a sixth aspect, the present invention provides a battery, comprising the negative electrode sheet described in the fourth aspect; and / or the separator described in the fifth aspect.
[0033] In a seventh aspect, the present invention provides a battery pack comprising the battery described in the sixth aspect.
[0034] In an eighth aspect, the present invention provides an electrical device, comprising the battery described in the sixth aspect or the battery pack described in the seventh aspect.
[0035] The battery activator provided by the present invention can continuously provide the battery cell with the additives required to form the SEI film, and can always keep the additive concentration in the electrolysis within a certain range, avoiding the difficulty and unevenness of lithium ion diffusion caused by excessively high additive content, thereby ensuring the capacity and cycle stability of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0037] Figure 1 A schematic diagram of the structure of a battery according to a specific embodiment of the present invention;
[0038] Figure 2 are interface diagrams of different battery cells, wherein a is an interface diagram of a battery cell prepared in control application example 1, b is an interface diagram of a battery cell prepared using the battery activator of Example 1 in application example 1, c is an interface diagram of a battery cell prepared using the battery activator of Example 1 in application example 2; d is an interface diagram of a battery cell prepared using the battery activator of Example 1 in application example 3;
[0039] Figure 3 It is a comparison chart of the cycle performance of the battery cell prepared in Control Application Example 1, the battery cell prepared using the battery activator of Example 1 in Application Example 1, the battery cell prepared using the battery activator of Example 1 in Application Example 2, and the battery cell prepared using the battery activator of Example 1 in Application Example 3. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0041] In a first aspect, the present invention provides a battery activator, comprising a shell and a sustained-release material encapsulated in the shell; the shell comprises a first polymer layer close to the sustained-release material and a second polymer layer away from the sustained-release material, the first polymer layer comprises a plurality of first micropores, the second polymer layer comprises a plurality of second micropores, the second polymer layer comprises a cross-linked polymer formed by cross-linking a CC unsaturated polymer, the pore size of the first micropore is not greater than 0.2 μm, and the pore size of the second micropore is not less than 0.5 μm.
[0042] The battery activator provided by the present invention can continuously provide the additives required for forming the SEI film for the battery cell, and can always keep the concentration of the additives within a certain range, avoiding the difficulty and unevenness of lithium ion diffusion caused by excessively high additive content, and the structure can ensure that there is always a uniform VC content at each position on the surface of the pole piece, avoiding the accelerated decay of the battery cell due to uneven VC, thereby ensuring the capacity and cycle stability of the battery cell. The main reasons include: the slow-release material can provide the additives required for SEI film formation for the battery cell, the first polymer layer is the first barrier for the slow-release material to release slowly, and its pore size only allows the additives in the slow-release material to enter and exit, while the molecules in the electrolyte are macromolecules existing in a solvated structure and cannot pass through the first polymer layer, the second polymer layer is the second barrier for the slow-release material to release slowly, and the slow-release material can achieve long-term slow release after flowing out of the first polymer layer and then passing through the second polymer layer, so that the additives in the electrolyte are always kept in a specific concentration range, avoiding the difficulty and unevenness of diffusion caused by high additive content. In addition, traditional additives are generally dispersed in the electrolyte, and the additives are very likely to be mainly distributed at the bottom of the battery cell or on the outermost aluminum-plastic film of the electrode core, and cannot diffuse to the middle of the electrode sheet, resulting in uneven current distribution in the battery cell and prone to center cracking of the battery cell. However, since the second polymer layer of the present invention includes a cross-linked polymer, the battery activator of the present invention can be stretched into a film and directly used as a diaphragm or adhered to a diaphragm or a negative electrode sheet, thereby ensuring uniform distribution of the additives in the battery cell and further extending the service life of the battery.
[0043] In an optional embodiment, the sustained-release material is in a semi-gel or gel state, wherein the semi-gel or gel sustained-release material can serve as a third barrier for sustained-release rate control of the sustained-release material, thereby further ensuring that the concentration of the additive is within a certain range and realizing long-term sustained-release of the additive.
[0044] In an optional embodiment, the pore size of the first micropore is 0.001 μm-0.2 μm, and the pore size of the second micropore is 0.5 μm-1 μm.
[0045] Exemplarily, the pore size of the first micropore is 0.001μm, 0.002μm, 0.005μm, 0.007μm, 0.01μm, 0.02μm, 0.03μm, 0.04μm, 0.05μm, 0.06μm, 0.07μm, 0.08μm, 0.09μm, 0.1μm, 0.12μm, 0.15μm, 0.16μm, 0.17μm, 0.18μm, 0.19μm, 0.2μm, etc., or a range formed by any two of them, and the pore size of the second micropore is 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, etc., or a range formed by any two of them.
[0046] In an optional embodiment, the additive required for forming the SEI film includes at least one of vinylene carbonate (VC), propane sultone (PS), methylene disulfate (MMDS), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC);
[0047] And / or, the additive accounts for 50%-70% of the weight of the sustained-release material.
[0048] In some embodiments, the sustained-release material is composed of additives required for forming a SEI film and a gelling agent, and the gelling agent includes at least one of ethylene carbonate, gelatin, agar, and the like.
[0049] In an optional embodiment, the first polymer layer includes a polymer substrate and a first additive, the polymer substrate includes at least one of polypropylene, polystyrene, and polycarbonate; the first additive includes at least one of a sulfonic acid polymer, a phosphate polymer, and a silicon-alkoxy polymer.
[0050] Among them, the first additive of the above embodiment can continue to play the repair function of SEI film after the additive in the slow-release material is consumed, and the reason is that the sulfonic acid group and the phosphoric acid group polymer can reduce the sulfonic acid group and the phosphoric acid group that form the SEI film, thereby repairing the SEI film. The silicon-based-alkoxy polymer itself has a high reduction potential, and in the presence of the slow-release material, it does not directly reduce the main components of the SEI film, but it can reduce the rupture and regeneration of the SEI film on the interface of the negative electrode material in the battery due to moisture or acidity by adsorbing moisture or acidity in the battery cell, thereby improving the cycle stability of the battery, and because the reduction potential of the sulfonic acid group polymer, the phosphoric acid group polymer, and the silicon-based-alkoxy polymer is lower than that of the additive in the slow-release material, therefore, it will not be reduced during the normal slow-release period of the slow-release material and can exist stably.
[0051] In an optional embodiment, the second polymer layer includes the hydrophobic cross-linked polymer, a second additive and / or a third additive, the second additive includes an isocyanate polymer and / or an epoxy polymer, and the third additive is a silicon-alkoxy polymer.
[0052] Among them, the hydrophobic cross-linked polymer can make the battery activator of the above embodiment more suitable for lithium-ion batteries, and the second additive has a water removal function, which helps to remove a small amount of water in the lithium-ion battery, thereby further enhancing the life of the battery cell, and the third additive can continue to play the repair function of the SEI film after the additive in the sustained-release material is consumed.
[0053] In an alternative embodiment, the structure of the silicon-alkoxy polymer is as shown in Formula 1:
[0054]
[0055] Wherein, R1 and R2 are each independently one of -OCH3, -N(CH3)CH3, and -NH-R3, R3 is a C1-C20 alkyl group, and n is greater than 0.
[0056] In some embodiments, n is any value from 1 to 200, any value from 2 to 100, any value from 5 to 50, and more specifically 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, etc.
[0057] In some embodiments, the method for preparing the silicon-alkoxy polymer comprises the following process:
[0058] In a vacuum or rare gas atmosphere, polydimethylsiloxane, tetramethoxysiloxane, monomethylamine, etc. are mixed in a mass ratio of 1:1.5, reacted at about 100°C, vacuum stirred for 30 minutes, and then water was added. After stirring and stratification, the upper layer product was taken, which is the silicon-alkoxy polymer.
[0059] In an alternative embodiment, the first additive accounts for 5%-8% by weight of the polymer substrate.
[0060] In an optional embodiment, the second additive accounts for 3%-5% of the weight of the cross-linked polymer; and / or the third additive accounts for 2%-5% of the weight of the cross-linked polymer.
[0061] Among them, the second additive has the effect of absorbing moisture and acidity; however, its content should not be too high. If the content is too high, it may cause the cross-linking structure content to decrease and the pore structure of the activator to be destroyed in the later stage of the cycle.
[0062] In some embodiments, the cross-linking degree of the CC unsaturated polymer is greater than 80%; and / or the sustained release rate of the battery activator is 1 to 1000 μg / day.
[0063] The sustained release rate can satisfy the continuous repair of SEI membrane by VC during the cycle. The crosslinking degree of CC unsaturated polymer can be obtained by calculation, for example: crosslinking degree = m (crosslinking agent + additive crosslinking mass) / m (crosslinking agent + additive addition amount).
[0064] In a first aspect, the present invention provides a method for preparing the above-mentioned battery activator, comprising the following steps:
[0065] 1) The additives and gelling agent required for forming the SEI film are mixed to obtain a semi-gel or gel-state sustained-release material;
[0066] 2) adding the sustained-release material to a dispersion liquid including a polymer substrate, a first additive, a dispersant, and a solvent, performing a mixing process to obtain a mixed system, and volatilizing the solvent of the mixed system to obtain a sustained-release material wrapped with the first polymer layer; wherein the solid content of the mixed system is 30-40%, and the volatilization rate of the solvent is greater than 2750 cm / h;
[0067] 3) adding the sustained-release material wrapping the first polymer layer to a dispersion liquid including CC unsaturated polymer, the second additive and / or the first additive cross-linking curing agent, and a solvent, and performing a cross-linking reaction at 50° C.-70° C. to obtain the battery activator.
[0068] The volatilization rate of the above-mentioned solvent is a vacuum volatilization rate; in some embodiments, the volatilization rate of the solvent is 2800-3000 cm / h (vacuum volatilization rate).
[0069] In some embodiments, the content of the first additive is 1-3%, and the first additive can assist in the pore formation of the first polymer layer.
[0070] Exemplarily, the gelling agent can be any substance that can make the additive into a semi-gel state, including but not limited to: ethylene carbonate, gelatin, agar, etc.; the dispersant includes but is not limited to: sodium methylene cellulose, triethylhexyl phosphate, sodium dodecyl sulfate, etc.; the solvents in step 2) and step 3) can be the same or different, preferably a volatile solvent, including but not limited to: dichloromethane, ethanol, etc.; the cross-linking curing agent is any curing agent that can accelerate the cross-linking of CC unsaturated polymers, including but not limited to: polyamide cross-linking curing agents, aliphatic amine cross-linking curing agents, aromatic amine cross-linking curing agents, etc.
[0071] The time of the cross-linking reaction is not particularly limited in the present invention, and the technician can adjust it according to the degree of cross-linking. For example, when the mass of the CC unsaturated polymer is 100g, the temperature of the cross-linking reaction is 50-70°C and the time is 48h.
[0072] The amount of the cross-linking curing agent added is not particularly limited in the present invention, and can be adjusted by technicians according to the required cross-linking rate. For example, the mass ratio of the cross-linking curing agent to the CC unsaturated polymer is 20%-40%.
[0073] In a third aspect, the present invention provides an activation membrane formed by the battery activator described in the first aspect.
[0074] In some embodiments, the activated membrane is prepared by the following process:
[0075] An appropriate amount of battery activator is added into a high-speed mixer for stirring, and the obtained material is calendered by an electric heated roller press to prepare the activated film;
[0076] Exemplarily, the high mixer speed is 200-1000 r / min, and the mixing time is 1h-5h; during the calendering process, the gap width between the two hot pressing rollers is 1-500 μm, the roller speed is 1.0m / min to 5m / min, and the roller temperature is 40-80°C.
[0077] In addition, the thickness of the activated film can be adjusted by adjusting the parameters of the calendering process. In a specific embodiment of the present invention, the thickness of the activated film is 100-150 μm.
[0078] In a fourth aspect, the present invention provides a negative electrode sheet, comprising a current collector, and a negative electrode material layer and an activation membrane sequentially disposed on at least one surface of the current collector, wherein the activation membrane is the activation membrane described in the first aspect.
[0079] For example, the thickness of the activation membrane may be 1-3 μm. If it is too thick, the impedance of the battery cell will increase, and if it is too thin, the semi-permeable membrane structure inside the cross-linked structure may be over-compressed and deformed, and even the permeation rate may be accelerated.
[0080] It can be understood that the above-mentioned negative electrode material layer also includes a negative electrode active material and optionally a binder. The negative electrode active material is a variety of negative electrode active materials that can be inserted and removed by lithium commonly used by technicians in the field. For example, it can be selected from one or more of carbon materials, tin alloys, silicon alloys, silicon, tin, and germanium; the carbon material can be non-graphitized carbon, graphite, or carbon or pyrolytic carbon obtained by high-temperature oxidation of polyacetylene polymer materials, coke, organic polymer sintered products, activated carbon, etc. One or more; when the negative electrode active material uses silicon materials, the negative electrode coating also contains a conductive agent, which is a material commonly used by technicians in the field that can enhance electron transport. For example, it can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, graphene, etc.; the binder can be selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, polyethylene oxide, and ethylene oxide-propylene oxide copolymer.
[0081] In a fifth aspect, the present invention provides a diaphragm, which is the activation membrane described in the third aspect; or, comprises a diaphragm base layer and an activation membrane, wherein the activation membrane is arranged on a side of the diaphragm base layer close to the negative electrode sheet, and the activation membrane is the activation membrane described in the first aspect.
[0082] For example, when the activated membrane is used directly as a diaphragm, the thickness of the activated membrane can be 1-15 μm. If it is too thick, it may increase the impedance of the battery cell, and if it is too thin, it may cause the semipermeable membrane structure inside the cross-linked structure to be over-compressed and deformed, and even cause the permeation rate to accelerate; when the activated membrane and the traditional diaphragm are stacked, the thickness of the activated membrane can be 1-5 μm; if it is too thick, it will increase the impedance of the battery cell, and if it is too thin, it will cause the semipermeable membrane structure inside the cross-linked structure to be over-compressed and deformed, and even cause the permeation rate to accelerate.
[0083] The present invention has no particular limitation on the above-mentioned diaphragm substrate, and any known porous structure diaphragm substrate with electrochemical stability and chemical stability can be selected, for example, it can be at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.
[0084] In a sixth aspect, the present invention provides a battery, comprising the negative electrode sheet described in the fourth aspect or the separator described in the fifth aspect.
[0085] It should be noted that the above-mentioned batteries may include but are not limited to single cells, battery modules, battery packs, etc., that is, the actual application form of the battery provided by the present invention can be but is not limited to the listed products, and can also be other application forms. When the battery is a single cell, it includes at least one of a cylindrical battery, a square battery, etc.
[0086] In some embodiments, the battery includes a positive electrode sheet, a negative electrode sheet, and the separator described in the fifth aspect, and the schematic structural diagram thereof is shown in Figure 1 the figure shown.
[0087] It can be understood that the above positive electrode sheet includes a current collector and a positive electrode material layer sequentially disposed on at least one surface of the current collector. The positive electrode material layer includes a positive electrode active material, a conductive agent, and optionally a binder. The positive electrode active material is selected from at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium iron phosphate (LiFePO4), lithium cobalt phosphate (LiCoPO4), lithium manganese phosphate (LiMnPO4), lithium nickel phosphate (LiNiPO4), lithium manganate (LiMnO2), binary material LiNi x A (1-x) O2 (wherein A is selected from one of Co and Mn, 0 < x < 1), ternary material LiNimBnC (1-m-n) O2 (wherein B and C are independently selected from at least one of Co, Al, and Mn, and B and C are different, 0 < m < 1, 0 < n < 1); the conductive agent is a material commonly used by those skilled in the art that can enhance the electron transfer function. For example, it can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, graphene, carbon fiber, carbon nanotube, and Ketjen black, etc.; the binder can be selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polycarbonate propylene ester, styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, poly(ethylene oxide), ethylene oxide-propylene oxide copolymer, polyethylene, polypropylene, polyamideimide, polyvinyl alcohol, and sodium polyacrylate.
[0088] The thickness and surface density of the above positive electrode sheet and negative electrode sheet are not specifically limited in the present invention. However, in order to balance the battery capacity, cycle life, and energy density, in a specific embodiment, the thickness of the positive electrode sheet or the negative electrode sheet is 20 - 120 μm, specifically including but not limited to: 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc.; the surface density of the positive electrode sheet or the negative electrode sheet is 2 - 25 mg / cm 2 , specifically including but not limited to: 3.5 mg / cm 2 , 4 mg / cm 2 , 4.5 mg / cm 2 , 5 mg / cm 2 , 5.5 mg / cm 2 , 6 mg / cm 2 , 6.5 mg / cm 2 , 7 mg / cm 2 , 7.5 mg / cm 2 , 8 mg / cm 2、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 mg / cm 2 、10mg / cm 2 、10.5mg / cm 2 、11mg / cm 2 、11.5mg / cm 2 , 12mg / cm 2 , 12.5mg / cm 2 、13mg / cm 2 、13.5mg / cm 2 、14mg / cm 2 、14.5mg / cm 2 、15mg / cm 2 、16mg / cm 2 、17mg / cm 2 、18mg / cm 2 、18mg / cm 2 、19mg / cm 2 , 20mg / cm 2 , 21mg / cm 2 , 22mg / cm 2 , 23mg / cm 2 , 24mg / cm 2 , 25mg / cm 2 wait.
[0089] In a seventh aspect, the present invention provides a battery pack comprising the solid-state battery described in the sixth aspect.
[0090] In an eighth aspect, the present invention provides an electrical device, comprising the battery described in the sixth aspect or the battery pack described in the seventh aspect.
[0091] It should be noted that the above-mentioned electronic equipment can be any conventional equipment that requires electricity, for example, including but not limited to computers, electric cars, air conditioners, refrigerators, washing machines, microwave ovens, printers, fax machines, etc.
[0092] The present invention is further described below in conjunction with specific embodiments:
[0093] The sources of some raw materials involved in the following experiments are shown in Table 1:
[0094] Table 1:
[0095] name Buy CAS Number Molecular weight Glass transition temperature Polypropylene CAS:9003-07-0 42.0804 - Polystyrene CAS:9003-53-6 104.1491 - Polycarbonate CAS:25037-45-0 290.311 - Polyphosphate CAS:5945-33-5 692.63 - Sulfonated Styrene CAS:9037-24-5 138.9911 - Polyacrylate CAS:228863-31-8 1511.47994661331 287K styrene CAS:1321-74-0 104.14 295K Hexamethylene diisocyanate CAS:822-06-0 168.19 - Metaphenylenediamine CAS:108-45-2 108.14 -
[0096] In Table 1, “-” means that this parameter is not recorded.
[0097] Example 1
[0098] This example provides a battery activator, comprising a shell and a sustained-release material encapsulated in the shell; the shell comprises a first polymer layer close to the sustained-release material and a second polymer layer away from the sustained-release material, the first polymer layer comprises a plurality of first micropores, the pore size of the first micropores is about 0.1 μm; the first polymer layer comprises polypropylene and polyphosphate, wherein the mass ratio of polyphosphate to polypropylene is 3%;
[0099] The second polymer layer includes a plurality of second micropores, each of which has a pore size of about 0.5 μm; in terms of mass percentage, the second polymer layer includes a cross-linked polymer (cross-linking degree > 80%) formed by cross-linking CC unsaturated polymer polyacrylate, hexamethylene diisocyanate and a silicon-alkoxy polymer; the mass ratio of hexamethylene diisocyanate to the cross-linked polymer is 5%, and the mass ratio of the silicon-alkoxy polymer to the cross-linked polymer is 3%; the structure of the silicon-alkoxy polymer is as shown in Formula 1, wherein R1 is -OCH3, R2 is -N(CH3)CH3, and n is 2.
[0100] The sustained-release material is in a semi-gel state, and comprises 75 parts of vinylene carbonate (VC) and 25 parts of ethylene carbonate (EC) by weight;
[0101] The preparation method comprises the following steps:
[0102] 1) In a nitrogen atmosphere, polydimethylsiloxane and monomethylamine are reacted at a molar ratio of 1:1.5 at 100° C., and after vacuum stirring for 30 minutes, water is added, and after stirring and layering, the upper layer product is taken, i.e., the silicon-alkoxy polymer, and is set aside;
[0103] 2) the 75 g of vinylene carbonate and 25 g of vinylene carbonate were stirred at a speed of 300 rpm / s for 1 h to obtain a semi-gel sustained-release material;
[0104] 3) 20g of polypropylene, 5g of polyphosphate, 10g of diethylenetriamine and 65g of dichloromethane are mixed, and the sustained-release material is added to the mixed system to make the solid content of the mixed system 30-40%, and stirred at 40°C for 3h, the volatilization rate of dichloromethane is>2750cm / h, and after the dichloromethane is completely volatilized, the residual vinylene carbonate on the surface is washed with alcohol to obtain a sustained-release material wrapped with the first polymer layer;
[0105] 4) adding the sustained-release material wrapped in the first polymer layer obtained in step 3) to a dispersion liquid including 30 g of polyacrylate, 5 g of m-phenylenediamine, 60 g of dimethyl carbonate, 3 g of hexamethylene diisocyanate and 2 g of silicon-alkoxy polymer, stirring for 12 h at 50° C.-70° C. for cross-linking reaction, removing the solvent after the reaction, and washing the residual polyacrylate on the surface with alcohol to obtain the battery activator.
[0106] Example 2
[0107] This example provides a battery activator, which is basically the same as Example 1, except that: the first polymer layer does not contain polyphosphate; its preparation refers to Example 1, and the pore size of the first micropore is 1nm to 10nm.
[0108] Example 3
[0109] This example provides a battery activator, which is basically the same as Example 1, except that the second polymer layer does not contain hexamethylene diisocyanate; its preparation refers to Example 1.
[0110] Example 4
[0111] This example provides a battery activator, which is basically the same as Example 1, except that the second polymer layer does not contain a silicon-alkoxy polymer; its preparation is based on Example 1.
[0112] Example 5
[0113] This example provides a battery activator, which is basically the same as Example 1, except that: the sustained-release material is in a gel state, and its preparation refers to Example 1, except that: step 2) 75g of vinylene carbonate, 25g of EC, and 10g of ethylenetriamine are mixed, and stirred at a speed of 300rpm / s for 1h to obtain a gel-state sustained-release material.
[0114] Comparative Example 1
[0115] This example provides a battery activator, including a shell and a sustained-release material encapsulated in the shell; the shell is polystyrene, and the sustained-release material is the same as that in Example 1.
[0116] The preparation method comprises the following steps:
[0117] Polystyrene (PS) was dissolved in dichloromethane (DCM) to prepare 25 mL of dispersion (a). In addition, 250 mL of aqueous solution (b) was prepared, which included 5 wt% of ethylene dichloride (VC) and 0.5 wt% of gelatin as a stabilizer, and the dispersion (a) was added to the aqueous solution (b) to form an oil / water emulsion. Then, DCM was evaporated to obtain capsules containing VC, and the capsules thus obtained were washed several times with distilled water to prepare a battery activator.
[0118] Comparative Example 2
[0119] The only difference from Example 1 is that the second polymer layer is not included.
[0120] Test Example 1
[0121] The activation film is prepared using the battery activators of the above-mentioned embodiments and comparative examples, comprising the following steps:
[0122] The battery activator is dispersed in dimethyl carbonate to obtain slurry, which is extruded at a high temperature of 70°C, rolled into a thick sheet of a certain thickness, and the thick sheet is sequentially stretched longitudinally or transversely into an activated film of a desired thickness.
[0123] The tensile strength of the activated film with a thickness of 3 μm was tested to be ≥1500 kgf.
[0124] Application Example 1
[0125] A series of negative electrode sheets are provided. The negative electrode sheets include a current collector and a negative electrode material layer and an activation film sequentially arranged on at least one surface of the current collector. The activation film is the activation film prepared in Experimental Example 1 and has a thickness of 1 μm.
[0126] The preparation of the negative electrode sheet comprises the following steps:
[0127] 100g of sodium carboxymethyl cellulose aqueous solution (the mass ratio of sodium carboxymethyl cellulose to deionized water is 2wt%) is added to 100g of artificial graphite, and stirred under the action of a vacuum stirrer until the mixed system becomes a slurry with uniform fluidity, and then 3g of styrene-butadiene latex is added, and stirred under the action of a vacuum stirrer until the mixed system becomes a negative electrode slurry with uniform fluidity; the negative electrode slurry is evenly coated on the upper and lower surfaces of an aluminum foil with a thickness of 8μm; the coated aluminum foil is baked in an oven with different temperature gradients, and then dried in an oven at 120°C for 8h, and then rolled and cut to obtain a negative electrode sheet, wherein the single-side surface density of the negative electrode sheet is: 220mg / cm 2 , compacted density: 1.5g / cm 3 ; The above-mentioned activated film is evenly stacked on the negative electrode sheet in a stacking manner and lightly rolled (the setting range of the upper and lower platen hot pressing pressure is 8900kgf±100kgf).
[0128] This example also provides a series of battery cells
[0129] 1) Preparation of positive electrode sheet: positive electrode active material LiFePO4, polyvinylidene fluoride and acetylene black are mixed in a weight ratio of 95.7:0.96:1.91, and then PVDF slurry is added and stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 13 μm; the coated aluminum foil is baked in an oven with different temperature gradients, and then dried in an oven at 120°C for 8 hours, and then rolled and cut to obtain the desired positive electrode sheet, wherein the single-sided surface density of the positive electrode sheet is: 400 mg / cm 2 , compacted density: 2.4g / cm 3 );
[0130] 2) preparing an electrolyte: after mixing ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a mass ratio of 2:2:3, adding 5% of vinylene carbonate (VC) and 13% of lithium hexafluorophosphate (LiPF6) accounting for the total mass of the electrolyte, mixing and stirring to obtain an electrolyte;
[0131] 3) Each battery cell is composed of one electrode core, and each electrode core is composed of 7 positive electrode sheets prepared as above, 8 negative electrode sheets prepared as above and 16 separators (ion exchange membranes).
[0132] Application Example 2
[0133] This example provides a series of separators, including a 12 μm separator base layer and a 2 μm activation membrane. The activation membrane is arranged on a side of the separator base layer close to the negative electrode sheet. The activation membrane is the activation membrane of Experimental Example 1 (see Table 2 for details).
[0134] The preparation of a battery cell using the above-mentioned separator comprises the following steps:
[0135] Preparation of negative electrode sheet: add 100g of sodium carboxymethyl cellulose aqueous solution (the mass ratio of sodium carboxymethyl cellulose to deionized water is 2wt%) to 100g of artificial graphite, stir under the action of a vacuum stirrer until the mixed system becomes a slurry with uniform fluidity, then add 3g of styrene-butadiene latex, stir under the action of a vacuum stirrer until the mixed system becomes a negative electrode slurry with uniform fluidity; evenly coat the negative electrode slurry on the upper and lower surfaces of an aluminum foil with a thickness of 8μm; bake the coated aluminum foil in an oven with different temperature gradients, and then dry it in an oven at 120°C for 8h, and then roll and cut to obtain a negative electrode sheet, wherein the single-side surface density of the negative electrode sheet is: 220mg / cm 2 , compacted density: 1.5g / cm 3 ;
[0136] The positive electrode sheet and the electrolyte are the same as those in Application Example 1;
[0137] Each assembled battery consists of one pole core, and each pole core consists of 7 positive electrode sheets prepared as above, 8 negative electrode sheets prepared as above, and 16 separators (the separator consists of a 12μm ion exchange membrane and a 2μm activation membrane, and the activation membrane is arranged on the side of the ion exchange membrane close to the negative electrode sheet).
[0138] Application Example 3
[0139] The battery activator of Example 1 and Comparative Example 1 is directly added into the electrolyte, the negative electrode sheet and the separator do not include the battery activator, and the process of preparing the battery cell refers to Application Example 1.
[0140] Comparative Application Example 1
[0141] A battery cell is prepared using a negative electrode sheet and a separator that do not include an activation membrane, and the process is referred to Application Example 1.
[0142] Related tests:
[0143] The DCIR and cycle performance of the cells of the above application examples 1-3 and the control application example 1 were tested, and the results are recorded in Table 2. The test included the following process:
[0144] 50% SOC DC internal resistance test method: At room temperature 25±3℃, charge to 3.7V, 50% SOC with 1 / 3C constant current, discharge to 50% SOC with 1 / 3C constant current, and leave for 30min; discharge at 3C constant current for 10s, limit the cell to 2.2V, and detect 50% SOC DC internal resistance.
[0145] 100% DOD 45℃ cycle test method: 1C-100% DOD charge and discharge, that is, the test steps are 1C constant current and constant voltage charging to 3.7V, standing for 10 minutes, 1C discharge to 2.2V, and cycle 2000 times.
[0146] Table 2:
[0147]
[0148] It can be seen from Table 2 that, compared with the comparative example or the control group, the activation film prepared by the battery activator of the embodiment is used for the battery cell, which can significantly reduce the DCIR of the battery cell and has better cycle stability.
[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A battery activator, characterized in that: It comprises a shell and a sustained-release material encapsulated in the shell; the sustained-release material comprises additives required for forming an SEI film; the shell comprises a first polymer layer close to the sustained-release material and a second polymer layer away from the sustained-release material, the first polymer layer comprises a plurality of first micropores, the second polymer layer comprises a plurality of second micropores, the second polymer layer comprises a cross-linked polymer formed by cross-linking a CC unsaturated polymer, the pore size of the first micropore is not greater than 0.2 μm, and the pore size of the second micropore is not less than 0.5 μm.
2. The battery activator according to claim 1, characterized in that The sustained-release material is in a semi-gel state or a gel state; And / or, the pore size of the first micropore is 0.001 μm-0.2 μm, and the pore size of the second micropore is 0.5 μm-1 μm.
3. The battery activator according to claim 2, characterized in that The additives required for forming the SEI film include at least one of vinylene carbonate, propane sultone, methylene disulfate, vinyl ethylene carbonate, and fluoroethylene carbonate.
4. The battery activator according to any one of claims 1 to 3, characterized in that: The first polymer layer includes a polymer substrate and a first additive, wherein the polymer substrate includes at least one of polypropylene, polyvinylbenzene, and polycarbonate; and the first additive includes at least one of a sulfonic acid polymer, a phosphate polymer, and a silicon-alkoxy polymer.
5. The battery activator according to any one of claims 1 to 3, characterized in that: The second polymer layer includes the hydrophobic cross-linked polymer, a second additive and / or a third additive, the second additive is an isocyanate polymer and / or an epoxy polymer, and the third additive is a silicon-alkoxy polymer.
6. The battery activator according to claim 4 or 5, characterized in that: The structure of the silicon-alkoxy polymer is as shown in Formula 1: Wherein, R1 and R2 are each independently one of -OCH3, -N(CH3)CH3, and -NH-R3, R3 is a C1-C20 alkyl group, and n is greater than 0.
7. The battery activator according to claim 4, characterized in that The first additive accounts for 2% to 5% by weight of the polymer substrate.
8. The battery activator according to claim 5, characterized in that The second additive accounts for 2% to 5% by weight of the cross-linked polymer; And / or, the third additive accounts for 2%-5% by weight of the cross-linked polymer.
9. A method for preparing a battery activator as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: 1) The additives and gelling agent required for forming the SEI film are mixed to obtain a semi-gel or gel-state sustained-release material; 2) adding the sustained-release material to a dispersion liquid including a polymer substrate, a first additive, a dispersant, and a solvent, performing a mixing process to obtain a mixed system, and volatilizing the solvent of the mixed system to obtain a sustained-release material wrapped with the first polymer layer; wherein the solid content of the mixed system is 30%-40%, and the volatilization rate of the solvent is >2750cm / h; 3) adding the sustained-release material wrapping the first polymer layer to a dispersion liquid including a CC unsaturated polymer, a second additive and / or a third additive, a crosslinking curing agent, and a solvent, and performing a crosslinking reaction at 50° C.-70° C. to obtain the battery activator.
10. An activation membrane formed by the battery activator according to any one of claims 1 to 8.
11. A negative electrode sheet, characterized in that: The invention comprises a current collector and a negative electrode material layer and an activation film sequentially arranged on at least one surface of the current collector. The activation film is the activation film according to claim 10, and the thickness of the activation film is 1 μm to 10 μm.
12. A diaphragm, characterized in that: The diaphragm is the activation membrane as claimed in claim 10; or, comprises a diaphragm base layer and an activation membrane, wherein the activation membrane is arranged on a side of the diaphragm base layer close to the negative electrode sheet, and the activation membrane is the activation membrane as claimed in claim 10.
13. A battery, characterized in that: Comprising the negative electrode sheet according to claim 11; and / or, the separator according to claim 12.
14. A battery pack, characterized in that: Comprising the battery of claim 13.
15. An electrical equipment, characterized in that: Comprising the battery according to claim 13 or the battery pack according to claim 14.
Citation Information
Patent Citations
Lithium secondary battery containing capsule for controlled-release of additives
CN101213703A
Battery separator and method for producing same, and lithium ion secondary battery and method for producing same
CN102132442A
Polymer cell and preparation method thereof
CN103151563A
Lithium ion battery and electrolyte thereof
CN103441302A
Lithium metal cathode coated with solid polymer electrolyte and preparation method thereof
CN108511687A
Cited By
Battery activator and preparation method therefor, activation film, negative electrode sheet, battery, battery pack, and electric device
WO2026067565A1